2014
DOI: 10.1037/hea0000018
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of techniques that effectively change health behavior: Evidence from Meta-CART analysis.

Abstract: Objective: Many health-promoting interventions combine multiple behavior change techniques (BCTs) to maximize effectiveness. Although, in theory, BCTs can amplify each other, the available metaanalyses have not been able to identify specific combinations of techniques that provide synergistic effects. This study overcomes some of the shortcomings in the current methodology by applying classification and regression trees (CART) to meta-analytic data in a special way, referred to as Meta-CART. The aim was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 49 publications
4
131
1
Order By: Relevance
“…Looking more closely at the different intervention characteristics, results indicate effectiveness of interventions that focused on providing education and information was limited (with an effect size of d = .26) as compared with interventions that focused on improving self-regulatory skills (with an effect size of d = .42). A follow-up analysis (Dusseldorp, van Genugten, van Buuren, Verheijden, & van Empelen, 2014) examined whether specific combinations of intervention ingredients proved more effective than single strategies and found evidence that providing information about the health consequences of behaviour could in fact influence healthy eating and physical activity when combined with intention formation prompting. Interventions aimed at the 'rational' determinants of eating behaviour thus seem to be effective to some extent, but effect sizes are mostly within the small to medium range.…”
Section: Reflective Influencesmentioning
confidence: 99%
“…Looking more closely at the different intervention characteristics, results indicate effectiveness of interventions that focused on providing education and information was limited (with an effect size of d = .26) as compared with interventions that focused on improving self-regulatory skills (with an effect size of d = .42). A follow-up analysis (Dusseldorp, van Genugten, van Buuren, Verheijden, & van Empelen, 2014) examined whether specific combinations of intervention ingredients proved more effective than single strategies and found evidence that providing information about the health consequences of behaviour could in fact influence healthy eating and physical activity when combined with intention formation prompting. Interventions aimed at the 'rational' determinants of eating behaviour thus seem to be effective to some extent, but effect sizes are mostly within the small to medium range.…”
Section: Reflective Influencesmentioning
confidence: 99%
“…However, considering the long-term aspect and the complexity of behavior change (in contrast to a one-time act of compliance), we do not think that the most optimal solution to achieve behavior change is to focus on one (highest rated) strategy. Instead, we would suggest a combination [11] of highestrated strategies or interventions (for the user's features), to avoid repetition over longer period of times (in combination with plenty of variation of messages within a strategy), but also to maximize the effectiveness of the message that behavior change has benefits for that user [14]. This could still be modeled, as suggested by Kaptein [26], by making the model more complex, even without focusing on only the highest-rated strategies, but also on which combination of strategies results in the optimal outcome (the most "permanent" behavior change).…”
Section: System Design Considerationsmentioning
confidence: 99%
“…Reviews testing the efficacy of techniques designed to change behaviour, particularly combinations of techniques, could examine the effects of techniques aligned with a specific theory. For example, Michie, Abraham, Whittington, McAteer and Gupta [50] examined the efficacy of techniques derived from Control Theory [51] (Carver & Scheier, 1982); namely goal-setting, monitoring and feedback (see also Dusseldorp et al [52] ). Third, recent research has identified more novel, but promising determinants of health behaviour and its maintenance including implicit processes [53,54] , affect [55][56][57] , habit [58,59] , justifications or self-licensing [60,61] and compensatory beliefs [62] .…”
Section: Issue 4: Combining Theoriesmentioning
confidence: 99%